2023
DOI: 10.1021/acsbiomaterials.3c00408
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerization Parameters Influence Mechanical, Microstructural, and Cell Loading Properties of Rapidly Fabricated Cell Scaffolds

Abstract: Engineered scaffolds are commonly used to assist in cellular transplantations, providing crucial support and specific architecture for a variety of tissue engineering applications. Photopolymerization as a fabrication technique for cell scaffolds enables precise spatial and temporal control of properties and structure. One simple technique to achieve a two-dimensional structure is the use of a patterned photomask, which results in regionally selective photo-cross-linking. However, the relationships between pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Moreover, the photopolymerization parameters also affect the stiffness of the materials. Allen et al [ 141 ] examined the impact of light intensity and exposure time on scaffold properties, such as shear modulus and micropore structure, and found that light intensity and polymerization time directly impact the scaffold stiffness and micropore structure, which in turn influence the cell loading capacity of the scaffold.…”
Section: Interaction Between Scaffolds and Mscsmentioning
confidence: 99%
“…Moreover, the photopolymerization parameters also affect the stiffness of the materials. Allen et al [ 141 ] examined the impact of light intensity and exposure time on scaffold properties, such as shear modulus and micropore structure, and found that light intensity and polymerization time directly impact the scaffold stiffness and micropore structure, which in turn influence the cell loading capacity of the scaffold.…”
Section: Interaction Between Scaffolds and Mscsmentioning
confidence: 99%
“…Free radicals can be generated by employing thermally unstable molecules, such as azo compounds, 27 but also by irradiation (UV particularly) in the presence of a PI. 28 While materials prepared using this methodology are effective, the methodology requires harsh conditions that ultimately are not easy to reach due to the need to match several properties related to biocompatibility. 29 On the other hand, the synthesis approach to generate photocrosslinked biopolymers for biomedical use differs depending on the components and their medical purpose.…”
Section: Manuel Ahumadamentioning
confidence: 99%
“…Notwithstanding those above, in the presence of intrinsic (e.g., RF, 3-hydroxykynurenine) or extrinsic (e.g., RB, Irgacure) PSs, such as the ones used during photopolymerization, proteins, 44 lipids, 136 and DNA 137 can be modified. Although photo-oxidation has been successfully employed for medical purposes (e.g., photodynamic therapy and photo-tissue bonding, reviewed), 28,29 there also exists evidence that demonstrates that undesired photo-oxidation can lead to the oxidative modification of biomolecules with detrimental consequences for human health (commonly addressed to the presence of PS over PI). A recent report showed that the endogenous PS 3-hydroxykynurenine (Fig.…”
Section: Photo-reactions Side Effects When Applied In Situmentioning
confidence: 99%
See 1 more Smart Citation